What's in your plate?AMPA receptors modulation at the crossroads of homeostatic and hedonic eating - Maria Italia; Diego Scheggia; Monica DiLuca; Fabrizio Gardoni (Pharmacological Research)
Eating behaviors are governed by the complex interplay between homeostatic mechanisms, driven by metabolic needs, and hedonic pathways, supporting the rewarding aspects of food consumption. This review explores the role of AMPA-type glutamate receptors (AMPARs) in modulating both hedonic and homeostatic feeding, highlighting their contributions to reward sensitivity and metabolic regulation in specific neuronal circuitries and their putative role in eating disorders. In the nucleus accumbens, calcium-permeable AMPARs (Cp-AMPARs) mediate synaptic adaptations that enhance reward-seeking behavior under food restriction and after exposure to palatable diets. These molecular mechanisms resemble those observed in substance addiction, highlighting shared pathways between maladaptive eating and addictive behaviors. In hypothalamic circuits, AMPARs dynamically adjust synaptic composition in response to metabolic hormones, such as leptin and ghrelin, to maintain energy homeostasis, underscoring their role in fine-tuning hunger and satiety. Interestingly, peripheral metabolic signals and dietary states can modulate hippocampal synaptic plasticity through AMPAR-dependent mechanisms, thereby affecting meal-related memory formation and retrieval. Overall, these findings indicate the involvement of AMPAR in food-seeking behavior and, consequently, their potential role in eating disorders. However, despite the therapeutic potential of targeting AMPARs, available pharmacological strategies remain very limited. Preclinical data highlights new possible approaches, such as the development of AMPAR-allosteric and subunit-specific agents, yet challenges related to off-target effects in chronic treatments persist. By integrating insights into the neuroplastic mechanisms underlying feeding behaviors, this review lays the groundwork for advancing compounds targeting AMPARs for the therapy of metabolic and eating disorders.